A case report of Dermanyssus gallinae infestation in three cats. Issue 4 (30th April 2018) - Di Palma, Antonella; Leone, Federico; Albanese, Francesco; Beccati, Massimo
Abstract : Background: Dermanyssus gallinae is a major threat for the poultry industry; these mites also feed on the blood of many other birds, small mammals and potentially humans. Hypothesis/Objectives: Three cats with dermatitis attributed to D. gallinae infestation. Animals: Two 40‐day‐old kittens, living in a rural area, and one 7‐year‐old female indoor cat, were presented with a pruritic skin condition. Methods: Mite specimens were collected from the cats and examined by light and scanning electron microscopy. Cytological and histological examinations of the skin lesions were performed. Results: A diagnosis of D. gallinae infestation was made after identification of the mites. Histological findings were compatible with eosinophilic dermatitis. Clinical improvement was noted two weeks after treatment. Conclusions and clinical importance: The two kittens showed chronic blood loss which reflects the ability of D. gallinae mites to switch host. For the indoor cat, mites were presumed to be carried by birds regularly present on the balcony of the apartment. This demonstrates that mite infestation is possible even in urban areas, through contact with birds or their abandoned nests. When birds are not present, cats or other small mammals as well as humans, can be infested. Abstract : Background – Dermanyssus gallinae is a major threat for the poultry industry; the mites also feed on the blood of many other birds, small mammals and potentially humans.Hypothesis/Objectives – Three cats with dermatitis attributed to D. gallinae infestation.Conclusions and clinical importance – The two kittens showed chronic blood loss which reflects the ability of D. gallinae mites to switch host. For the indoor cat, mites were presumed to be carried by birds regularly present on the balcony of the apartment. This demonstrates that mite infestation is possible even in urban areas, through contact with birds or their abandoned nests. When birds are not present, cats or other small mammals as well as humans, can be infested.